Case Report: A Novel CACNA1A Mutation Caused Flunarizine-Responsive Type 2 Episodic Ataxia and Hemiplegic Migraine With Abnormal MRI of Cerebral White Matter - Yuan, Xiaoqiu; Zheng, Yiming; Gao, Feng; Sun, Wei; Wang, Zhaoxia; Zhao, Guiping (Frontiers in Neurology, 2022)
Episodic ataxia type 2 (EA2) is one autosomal-dominant neurological disorder characterized by debilitating attacks of ataxia. It is mainly caused by loss-of-function mutations of the CACNA1A gene, which encodes the pore-forming α1A subunit of Cav2.1 (P/Q type voltage-gated calcium channel). Sporadic hemiplegic migraine (SHM) is another rare disease involving CACNA1A variants, which seldom coexists with EA2. Here we report a novel pathogenic mutation in CACNA1A (c.3836dupA, exon23, p.Y1279X) of a sixteen-year-old female, who complained about paroxysmal dizziness, headache, and unsteady gait. Her brain MRI revealed a slightly atrophic cerebellum and numerous asymptomatic hyperintense lesions of the cerebral white matter. The diagnosis of EA2 combined with SHM was made. Administration of 5-mg flunarizine once daily at night effectively reduced the attacks and attenuated her symptoms in a month.